Individual Low-Energy Toroidal Dipole State in Mg 24 - Nesterenko, V. O.; Repko, Anton; Kvasil, J.; Reinhard, Paul-Gerhard (Physical Review Letters, 2018)
The low-energy dipole excitations in Mg24 are investigated within the Skyrme quasiparticle random phase approximation for axial nuclei. The calculations with the force SLy6 reveal a remarkable feature: the lowest IπK=1-1 excitation (E=7.92 MeV) in Mg24 is a vortical toroidal state (TS) representing a specific vortex-antivortex realization of the well-known spherical Hill's vortex in a strongly deformed axial confinement. This is a striking example of an individual TS which can be much more easily discriminated in experiment than the toroidal dipole resonance embracing many states. The TS acquires the lowest energy due to the huge prolate axial deformation in Mg24. The result persists for different Skyrme parametrizations (SLy6, SVbas, SkM∗). We analyze spectroscopic properties of the TS and its relation with the cluster structure of Mg24. Similar TSs could exist in other highly prolate light nuclei. They could serve as promising tests for various reactions to probe a vortical (toroidal) nuclear flow.
CRIS-Team Scopus Importer:2021-07-19